Comprehensive effects of integrated management on reducing nitrogen and phosphorus loss under legume-rice rotations. (10th August 2022) - Wang, Shaopeng; Guo, Shufang; Zhai, Limei; Hua, Lingling; Khoshnevisan, Benyamin; Wang, Hongyuan; Liu, Hongbin
Abstract: Paddy fields-based cropping systems are usually located in areas with dense water networks, so nitrogen (N) and phosphorus (P) losses from rice paddy fields caused by runoff might pose a serious pollution risk to their surrounding water bodies. However, current research over establishing a low fertilizer input paddy-based cropping system with comprehensive management for reducing runoff losses of N and P is insufficient. A five-year field trial was carried out with a rice-fava planting system in the Erhai Lake watershed from 2015 to 2019. Three treatments were designed namely chemical fertilizer plus manure (CMF), reduced chemical fertilizer combined with manure at the same application rate under CMF treatment (RF), and returning straw plus chemical and organic fertilizers at the same rate with RF treatment (RFS). The mean annual runoff losses of total N (TN) and total P (TP) range from 0.99 to 1.39 kg ha −1 yr −1 and 0.09–0.12 kg ha −1 yr −1 . Compared with CMF treatment, RF had lower runoff losses of TN and TP by 20.86% and 23.05%, respectively, but the yields and soil fertility were also reduced. After returning straw, soil organic carbon (SOC), TN, and crop yields were maintained or even increased, and runoff losses of TN and TP were further reduced by 9.48% and 7.41%, respectively, compared with RF. Therefore, the runoff losses of N and P decreased by selecting the rice-fava rotation system and reducing chemical fertilizer input through manure application and straw returning, which greatly reduced the surplus N and P in this system. Moreover, the temporal variation in the concentration of TN and TP, along with the N:P ratio approved the existence of potential risk caused by TN and TP losses to the watershed in the early stage of rice growth. Overall, in addition to taking field measures to reduce the N and P runoff losses from paddy fields, the runoff water with high N and P concentrations in early rice growth stage cannot be ignored. Highlights: Rice-fava system with low fertilizer maintained yield and had low environment risk. Straw returning ensured crop yields under substituting chemical fertilizer by manure. Combined of straw returning and manure substitution reduced nutrient runoff loss. Runoff N/P concentration and N:P ratio in early stage of rice may need interception.